A longitudinal study of empathy in pre-clinical and clinical medical students and clinical supervisors. Issue 1 (December 2016) - Mahoney, Sarah; Sladek, Ruth; Neild, Tim
Abstract Background Although appropriate empathy in health professionals is essential, a loss of empathy can occur during medical education. The structure of clinical learning may be one factor that is implicated in a loss of empathy. This study examines student and doctor empathy, and possible associations between empathy and the structure of clinical learning. Methods There were three groups of participants: medical students (n = 281), who completed a longitudinal survey consisting of the Jefferson Scale of Empathy and an open question about empathy at the beginning and end of the 2013 academic year; private doctors (medical practitioners) in South Australia (n = 78) who completed a survey consisting of the Jefferson Scale of Empathy and an open question about empathy at the end of the students' academic year; and doctors (medical practitioners) from public teaching hospitals (n = 72) in southern Adelaide, South Australia who completed a survey consisting of the Jefferson Scale of Empathy at the end of the students' academic year . Results Year one students' empathy scores at the end of the year (102.8 ± 17.7) were significantly lower than at the start of the year (112.3 ± 9.6)p < .05). There were no other significant differences in students' empathy scores by year groups or across the two time points. Empathy scores were almost identical for private and hospital clinicians and higher than average scores for students. Free-text comments highlighted the importance students and doctors place on empathy. Students described issues that adversely affected their empathy, including specific incidents, systemic issues, and course structure, but also described some positive role models. Doctors' comments focused on the importance of empathy but qualified its meaning in the therapeutic setting. Conclusion Medical students and practitioners alike ascribe importance to empathy in clinical practice, yet its developmental course remains poorly understood with possible decrement across the course of medical education. A more sophisticated understanding of empathy in medical students is needed, with attention to issues that might adversely impact on this crucial aspect of their development. Trial registration This was not undertaken as the research did not involve a health care intervention on human participants.